Burden of disease due to chemical intoxications in Cali (Colombia) - Jaramillo López, Carolina (2023)
Objective. To estimate the burden of disease due to chemical substances in Cali (Colombia). Methods. Secondary analysis was performed based on the databases on morbidity and mortality due to poisoning by chemical substances of the District Secretary of Health of Cali (Colombia), occurring during the period from 2018 to 2020. The standard methodology was used to estimate disabilityadjusted life years (DALYs) and the Poisson distribution to estimate the gaps. Results. During the period studied, men lost 1701 healthy life-years due to chemical poisonings, and women lost 895 years. The gap was OR 2.2 (2.0 - 2.4), higher in men than in women. Conclusions. There was a 14.5% increase in morbidity from chemical poisonings before the onset of the pandemic and a 53.9% reduction during the pandemic year by  COVID-19.